2012
DOI: 10.1089/jmf.2010.0329
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Content and Antioxidant Properties of Colored Soybean Seeds from Central Europe

Abstract: The antioxidant activity and contents of various polyphenol classes in the seeds of seven soybean varieties of different seed color and one yellow seed cultivar, representing a reference genotype, were evaluated. Total polyphenols and tannins were determined after extraction of plant material with 70% aqueous acetone, and total flavonoids were extracted with methanol and acetic acid, whereas anthocyanins were extracted with 20% aqueous ethanol. In addition, isoflavone content and composition were determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 32 publications
6
56
0
7
Order By: Relevance
“…Soybeans and soybean products are rich in polyphenols, in particular isoflavones (Malencic et al 2012), and the polyphenol content of wheat, which was added in larger amounts to diets in the second phase, is approximately three-fold lower in comparison with soybeans (Perez-Jimenez et al 2010). The antioxidant activity of apple pomace noted in this study was similar to that observed by other authors (Bai et al 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Soybeans and soybean products are rich in polyphenols, in particular isoflavones (Malencic et al 2012), and the polyphenol content of wheat, which was added in larger amounts to diets in the second phase, is approximately three-fold lower in comparison with soybeans (Perez-Jimenez et al 2010). The antioxidant activity of apple pomace noted in this study was similar to that observed by other authors (Bai et al 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Whent et al (2011), in a comparative study of total phenolic compounds in raw yellow and black soybean, found values varying from 3.5 to 4.9 mg GAE g -1 , which agree with those of the present study. Malencic et al (2012) observed a great variation of total phenolic compounds in the soybean cultivars, with contents ranging from 0.80 to 2.20 mg GAE g -1 in yellow soybean and from 0.81 to 12.10 mg GAE g -1 in black soybean.…”
Section: Resultsmentioning
confidence: 92%
“…Beans are frequently classified according to the colour of the seed coat, a characteristic that is genetically determined. Malenčić et al (2012) analysed eight coloured soybean varieties from central Europe for polyphenol and antioxidant content, including the isoflavones. There was no clear correlation between seed coat colour and isoflavone content, which is a conclusion shared by Kumar et al (2010).…”
Section: Factors Influencing Isoflavone Contentmentioning
confidence: 99%